Sublethal and transgenerational effects of synthetic insecticides on the biological parameters and functional response of Coccinella septempunctata (Coleoptera: Coccinellidae) under laboratory conditions - Afza, Rahat; Afzal, Ayesha; Riaz, Muhammad Asam; Majeed, Muhammad Zeeshan; Idrees, Atif; Qadir, Ziyad Abdul; Afzal, Muhammad; Hassan, Babar; Li, Jun (Frontiers in Physiology, 2023)
Synthetic insecticides have been an inevitable part of plant protection throughout the world. Sublethal effects of these chemicals on beneficial insect species are one of the contemporary issues these days. Using the age-stage, two-sex life table model, this study evaluated the sublethal and transgenerational effects of six synthetic insecticides (imidacloprid, thiamethoxam, lambda-cyhalothrin, cypermethrin, chlorpyrifos and profenofos) commonly applied to winter vegetables, on the fitness and predation of the seven-spotted ladybeetle, Coccinella septempunctata, which is an efficient predator of aphids worldwide. According to results, all insecticides at their sublethal doses (LC30) significantly suppressed the emergence of adults, adult weight, fertility and fecundity of the parental generation compared to control treatment. The larval stage was prolonged and oviposition, fecundity and total longevity of the adult beetles were decreased in unexposed progeny whose parents were exposed to sublethal doses of all insecticides. Moreover, the biological parameters of adults, including the intrinsic rate of increase (r), finite rate of increase (λ) and net reproductive rate (R0) were significantly reduced when exposed to sublethal doses of insecticides. The predation rate of the F1 generation adults was also decreased after exposure to the sublethal doses of insecticides. However, chlorpyrifos, profenofos, lambda-cyhalothrin and cypermethrin exhibited more deleterious effects on the fitness and population parameters of beetles than imidacloprid and thiamethoxam.